Regulación de vehículos eléctricos en el Ecuador: aspectos legales y garantía de Seguridad Jurídica - Morillo Gutiérrez, Alex Sebastián (2025)
This research analyzes the regulation of two- and three-wheeled electric vehicles in Ecuador, with a focus on legal aspects and the guarantee of legal security, taking into consideration that in the country, the lack of a specific regulatory framework has generated uncertainty for users and has limited the development of sustainable mobility. The research identifies the legal challenges derived from the absence of clear regulations, including legal loopholes that affect the circulation, operation and supervision of these vehicles, compromising both road safety and the protection of citizen rights. Through a comparative analysis, foreign regulations that regulate this type of vehicles are examined, highlighting their effectiveness in promoting technical standards, economic incentives and security measures, which allows identifying good practices applicable to the Ecuadorian context. As a result, key recommendations are proposed for the design of a comprehensive regulatory framework that contemplates minimum technical standards, specific road safety regulations and clear provisions to guarantee legal security for users. The creation of adequate infrastructure, economic incentives and control mechanisms that promote compliance with regulations is also suggested. The implementation of these measures strengthens the transition towards sustainable electric mobility and contributes to guaranteeing the fundamental rights of road and legal safety. In this way, the aim is to align Ecuadorian regulation with international trends in electric mobility, promoting inclusive, safe and sustainable development.